Escaping Death: Mitochondrial Redox Homeostasis in Cancer Cells - Ciccarese, Francesco; Ciminale, Vincenzo (Frontiers in Oncology, 2017)
Reactive oxygen species (ROS) are important signalling molecules that act through the oxidation of nucleic acids, proteins and lipids. Several hallmarks of cancer, including uncontrolled proliferation, angiogenesis and genomic instability, are promoted by the increased ROS levels commonly found in tumor cells. To counteract excessive ROS accumulation, oxidative stress and death, cancer cells tightly regulate ROS levels by enhancing scavenging enzymes, which are dependent on the reducing cofactor NADPH. This Review focuses on mitochondrial ROS homeostasis, with a description of six pathways of NADPH production in mitochondria and a discussion of the possible strategies of pharmacological intervention to selectively eliminate cancer cells by increasing their ROS levels.